Penerapan E-Learning dalam Proses Pembelajaran pada Program Studi PAI Universitas Islam Negeri Raden Fatah Palembang - Alimron Alimron (Hayula: Indonesian Journal of Multidisciplinary Islamic Studies, 2019)
This study aims to describe how the application of e-learning in the learning process in the study program of PAI in UIN Raden Fatah, Palembang. This research is field research using a qualitative approach. The methods of data are observation, interviews, questionnaires, and documentation. There are five aspects of implementing e-learning that is observed by assessing the perceptions of lecturers and students. The results of the study concluded that First, there are differences of views between lecturers and students about the application of e-learning, only some lecturers have sufficient knowledge about e-learning applications, on the contrary, most of the students understand the application of e-learning. In the aspect of ease of use of e-learning applications, some lecturers said that they had difficulties in implementing e-learning, whereas most of the students said that they are able to implement e-learning. The other three aspects; the aspect of component of e-learning features, the usefulness of it, both lecturers and students assessing the positive and relatively good assessment, while they assessed less optimal about facilities supporting it.